A Qualitative Investigation of Australian Young Adult Responses to Pictorial and Graphic Alcohol Product Warnings. (October 2017) - Coomber, Kerri; Hayley, Alexa; Giorgi, Caterina; Miller, Peter G.
This qualitative study aimed to understand whether pictorial and graphic alcohol warnings would be an effective intervention to reduce alcohol-related harms among young adult drinkers. Four focus groups ( n = 26) were conducted examining impressions, reactions, and thoughts about five pictorial warnings and five graphic warnings. Students (58% female) from Melbourne, Australia, aged 18 to 25 years who consumed alcohol participated. The warnings used in this study elicited strong negative emotional reactions, including avoidance. While the use of images increased the salience of the warnings, participants discussed the likelihood of habituation, indicating warning rotation is needed. Targeted messages and statistics appealed to the participants. However, they were unlikely to change their drinking behavior due to the warnings. Consistent with tobacco warning literature, and in line with behavior change and message persuasion theory, warning labels with photographic images and targeted statistics were found to have the most persuasive impact against risky drinking within this sample.